Cell sheet composed of adipose-derived stem cells demonstrates enhanced skin wound healing with reduced scar formation. (1st September 2018) - Yu, Jiashing; Wang, Ming-Yang; Tai, Hao-Chih; Cheng, Nai-Chen
Graphical abstract: Abstract: Scar formation remains a major clinical concern following tissue injuries such as skin wounds. Adipose-derived stem cell (ASC) sheets can be fabricated quickly through stimulation with l -ascorbate 2-phosphate and have valuable applications in tissue regeneration and wound healing. However, the antifibrotic capability of ASCs in cell sheet format has not been sufficiently investigated. We employed a murine model of healing-impaired cutaneous wounds and observed faster wound healing with ASC sheet treatment. Significantly more engrafted ASCs were observed in the wound tissue treated with ASC sheets at 14 days after wounding compared with dissociated cells. Moreover, no ASCs were found at day 28, which indicated a minimal risk of long-term side effects. The neoskin formed in the presence of ASC sheets exhibited a thickness comparable to normal skin and possessed a highly organized collagen structure. ASC sheets also suppressed macrophage infiltration and modulated TNF-α and TGF-β1 expression in vivo . Examination of fibroblasts cultured in ASC-conditioned medium indicated an anti-scarring effect of the ASC sheets evidenced by the downregulation of TGF-β1 and α-SMA in fibroblasts, which was likely mediated through the increased secretion of hepatocyte growth factor. Moreover, ASC sheets secreted significantly more C1q/TNF-related protein-3, which inhibited the C-C motif ligand 2 release by macrophages in vitro and subsequently reduced the chemotaxis of unstimulated macrophages. This mechanism may account for the observed decrease in recruitment of macrophages into the wound tissue. We conclude that ASC sheets possess the necessary paracrine factors to improve skin wound healing with a superior neoskin quality. Statement of Significance: Adipose-derived stem cell (ASC) sheets exhibit great potential for tissue regeneration. In this study, we investigated whether ASC sheets can ameliorate skin wound healing with reduced scar formation, and faster wound healing was observed when applying ASC sheets in an impaired wound healing model of mice. The neoskin formed in the presence of ASC sheets exhibited a thickness comparable to normal skin with a more organized collagen structure. In vitro experiments suggested that the anti-scarring effect of the ASC sheets was partly mediated through increased secretion of hepatocyte growth factor. Moreover, ASC sheets secreted significantly more C1q/TNF-related protein-3, which may account for the decreased recruitment of macrophages into the wound tissue. Therefore, ASC sheets possess the necessary paracrine factors to improve skin wound healing with less scarring, thus representing a desirable method of topical wound treatment.